CATEGORIAL AFFILIATION AND SYNTACTIC FUNCTION OF REPETITIONS - M.G . Safarova (International Journal of Innovative Technologies in Social Science, 2023)
Some authors classify reduplication from the structural point of view, from which parts of speech they have been derived. The statistic results of such classification allows to determine which parts of speech have broader reduplication opportunities. A great deal of languages belonging to different language families, have been involved into investigation. From the syntactical point of view, reduplications are mainly act in the function of subject, object, and adverb, with the minority of attribute and predicate.